2007
DOI: 10.1038/labinvest.3700679
|View full text |Cite
|
Sign up to set email alerts
|

Role of aggregated medin in the pathogenesis of thoracic aortic aneurysm and dissection

Abstract: The pathogenesis of sporadic thoracic aortic aneurysm and dissection, which may lead to rupture of the aorta, remains largely unknown. Amyloid deposits, formed from the medin peptide, are very prevalent in the media of the thoracic aorta. We have studied the occurrence of medin-derived amyloid in specimens from patients with thoracic aortic aneurysm, aortic dissection type A and normal dimensioned aorta. Surprisingly, the amount of amyloid was significantly lower in the aneurysm and dissection groups (0.63±0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 43 publications
7
54
1
Order By: Relevance
“…[17][18][19] Degeneration and a decrease in thickness of the vessel wall were reported to be the main characteristic histological changes in aortic aneurysm. 20 In contrast, our results showed hypertrophy in the vessel wall compared to the control group ( Figure 2). This result is not relevant to the natural history of aortic aneurysm, and this difference might be due to the duration of the study.…”
Section: Discussioncontrasting
confidence: 79%
“…[17][18][19] Degeneration and a decrease in thickness of the vessel wall were reported to be the main characteristic histological changes in aortic aneurysm. 20 In contrast, our results showed hypertrophy in the vessel wall compared to the control group ( Figure 2). This result is not relevant to the natural history of aortic aneurysm, and this difference might be due to the duration of the study.…”
Section: Discussioncontrasting
confidence: 79%
“…It is well-known that PDGF-BB is not only a potent mitogen for VSMC, but also a key cellular chemoattractant in arterial restructuring [5], suggesting that MFG-E8 plays a crucial role in arterial remodeling. Indeed, MFG-E8 signaling is involved in both cardiovascular development and cardiovascular diseases (Table 1) [14, 15, 1719, 23, 24, 26, 37, 4352]. …”
Section: Introductionmentioning
confidence: 99%
“…Peng et al reported that the amount of medin-derived amyloid deposited in the aortic media was lower, and that of nonamyloid medin was higher, in aortic dissection patients than in a control group. 29) Medin amyloid is commonly found in the aortic media of individuals older than 50 years of age, and is a molecule in close contact with elastic fibers. Medin, an immature amyloid, has been suggested to be cytotoxic, and the possibility has been noted that medin may act on smooth muscle cells to increase the expression of matrix metalloproteinase (MMP)-2 in aortic dissection patients, thereby promoting the degradation of elastin and collagen.…”
Section: Elastic Fiber and Elastin Abnormalities In Aortic Dissectionmentioning
confidence: 99%